Adjusting tertiary mental health education during Covid-19: an Australian experience - Sebastian Rosenberg; Luis Salvador-Carulla; Lyndall Strazdins; Natasha Katruss (Instituto Nacional de Salud Pública, 2022)
Globally, tertiary education has been greatly affected by the Covid-19 crisis. In this essay we explore the impact of the pandemic on this educational sector in an Australian setting; specifically, we discuss how the Research School of Population Health at the Australian National University adjusted and adapted to the changing circumstances arising from the pandemic. In this respect, two adjustments (both described in detail in the text) in the way mental health education was delivered at the School were proposed to mitigate the impact of Covid-19 and enhance the university's capacity to provide quality public health education to students. Thus, this essay shows that it is possible to design educational interventions that surmount the challenges posed by the pandemic. In addition, educators may use the examples cited in this paper to guide them to respond appropriately to the challenges that have arisen in terms of health education due to Covid-19.